Niveles del Síndrome de Burnout en profesoras de educación inicial sector Callao - Soto Carrillo, Rosa Gladys (2012)
The purpose of this descriptive research was to determine the level of burnout syndrome in early childhood education teachers Callao area, dimensions: emotional exhaustion, depersonalization and personal accomplishment. The sample was available 153 teachers formed public educational institutions of the initial level of Callao, the instrument used was the Maslach Burnout Inventory (MBI) Maslach & Jackson 1981/1986). The emotional exhaustion scores were 73.9% in the low, 18.3% in the average and 7.8% in the high level, 83% in depersonalization is in the low, 10.5% in the middle and the 6.5% in high, low personal accomplishment in 11.1% level is low, at 28.1% on average and 60.8% in the high level. The teachers of Callao apparently have low levels of burnout.